2020
DOI: 10.1111/jonm.12907
|View full text |Cite
|
Sign up to set email alerts
|

Value, knowledge and implementation on evidence‐based practice among nurse managers in china: A regional cross‐sectional survey

Abstract: Aim To describe the value, knowledge and implementation of evidenced‐based practice (EBP) among Chinese nurse managers and explore its influencing factors. Background Although much of literature have reported the importance of nurse managers in pushing EBP progress and encouraged them to engage in EBP activities, the extent to which nurse managers engage in EBP is unclear. Methods A cross‐sectional web‐based survey was applied to 1,166 nurse managers recruited from 54 hospitals in Guangdong Province, China. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 41 publications
6
36
0
5
Order By: Relevance
“…This shows that the RNMs viewed EBP positively and their attitude towards EBP seemed to be more positive than their knowledge/skills and use of EBP. This result is consistent with previous studies describing attitude, practices and knowledge/skills associated with EBP (1,2,(34)(35)(36). Over 80% of the respondents agreed that EBP was 'fundamental to professional practice'.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…This shows that the RNMs viewed EBP positively and their attitude towards EBP seemed to be more positive than their knowledge/skills and use of EBP. This result is consistent with previous studies describing attitude, practices and knowledge/skills associated with EBP (1,2,(34)(35)(36). Over 80% of the respondents agreed that EBP was 'fundamental to professional practice'.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…We also found that if there is a lack of leadership, there will be many barriers, but if there is leadership support, many of these barriers will be resolved efficiently. A recent study found that nurse managers are positive about EBP, but they lacked the EBP knowledge and rarely implemented EBP (Chen, Wu, Zhou, Li, & Zhao, 2020). Therefore, if we want to reduce barriers, we need leadership, and if we want to implement evidence for leadership participants, we should educate or train nurse managers.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, YazdiMoghaddam et al [26] reported that ICU nurses must have skills and knowledge that enable them to understand the concept and diagnosis of brain death, without any religious or cultural beliefs opposing organ donation, being well informed of the care process and how to interact with the families. Furthermore, Chen et al [36] described how nursing managers should have experience in the implementation of evidence-based practice. Also, Zendrato et al [37] reported the characteristics of an effective manager: communication skills, leadership, education, work duration, and work experience.…”
Section: Discussionmentioning
confidence: 99%